2013
DOI: 10.1128/jcm.03166-12
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Methicillin-Resistant Staphylococcus aureus Isolates from Retail Meat and Humans in Georgia

Abstract: There is increasing interest in the presence of Staphylococcus aureus, specifically methicillin-resistant S. aureus (MRSA), on retail meat products. In this study, staphylococci were isolated from retail pork and retail beef in Georgia, and MRSA from the products was compared to human MRSA from the same geographic area using broth microdilution antimicrobial susceptibility testing, multilocus sequence typing (MLST), spa typing, SCCmec typing, and pulsed-field gel electrophoresis (PFGE). S. aureus was isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
102
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(126 citation statements)
references
References 48 publications
19
102
4
1
Order By: Relevance
“…Absence of the PVL gene in the cases of food poisoning has been reported previously [22]. [23] reported similar results for the high prevalence of SCCmec IV in retail meat samples. They reported that all of the MRSA strains of beef and pork samples were positive for SCCmec IV which was higher than our findings.…”
Section: Discussionsupporting
confidence: 85%
“…Absence of the PVL gene in the cases of food poisoning has been reported previously [22]. [23] reported similar results for the high prevalence of SCCmec IV in retail meat samples. They reported that all of the MRSA strains of beef and pork samples were positive for SCCmec IV which was higher than our findings.…”
Section: Discussionsupporting
confidence: 85%
“…The isolation of MRSA from different meat samples was reported previously from different countries (16)(17)(18)(19)(20)(21)(22)(23). Another study (10) reported MRSA strains from poultries in Iran; therefore, the isolation of MRSA strains from chicken meat was not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, S. aureus can be found commonly in various foods including meat (de Boer et al 2009, Jackson et al 2013) and fish (Da Silva et al 2010, Saito et al 2011. It is clear that contamination of food with this pathogen is often related to improper handling and storage conditions, as well as inadequate hygienic conditions and post-production microbial contamination (Ray 2004).…”
Section: Introductionmentioning
confidence: 99%
“…aureus causes serious diseases by producing various virulence factors and presents difficult therapeutic problems due to rapid development of resistance to many antimicrobial agents. The results of many studies on genetic diversity of S. aureus from different regions have been documented (Soltan et al 2010, Jackson et al 2013, Alibayov et al 2014. In Turkey, limited data are available on genotypic characterization of S. aureus from fish and meat.…”
Section: Introductionmentioning
confidence: 99%